Polaribacter undariae sp. nov., isolated from a brown alga reservoir - Sooyeon Park; Jimin Park; Yong-Taek Jung; Kang Hyun Lee; Jung‐Hoon Yoon (2015)
A Gram-stain-negative, non-flagellated, non-gliding, aerobic and rod-shaped or ovoid bacterial strain, designated W-BA7 T , was isolated from a brown alga reservoir on the South Sea in South Korea. This strain grew optimally at 25 °C, at pH 7.0–8.0 and in the presence of approximately 2.0 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences showed that strain W-BA7 T belonged to the genus Polaribacter , clustering coherently with the type strain of Polaribacter sejongensis , showing 99.3 % sequence similarity. Strain W-BA7 T exhibited 16S rRNA gene sequence similarity of 93.4–98.6 % to the type strains of the other species of the genus Polaribacter . Strain W-BA7 T contained MK-6 as the predominant menaquinone and iso-C 15 : 0 3-OH and anteiso-C 15 : 0 as the major fatty acids. The major polar lipids of strain W-BA7 T were phosphatidylethanolamine, three unidentified lipids, one unidentified glycolipid, one unidentified aminolipid and one unidentified aminophospholipid. The DNA G+C content of strain W-BA7 T was 31.9 mol%, and the mean DNA–DNA relatedness with the type strains of four phylogenetically related species of the genus Polaribacter was 12–27 %. Differential phenotypic properties, together with its phylogenetic and genetic distinctiveness, revealed that strain W-BA7 T is separated from recognized species of the genus Polaribacter . On the basis of the data presented, strain W-BA7 T is considered to represent a novel species of the genus Polaribacter , for which the name Polaribacter undariae sp. nov. is proposed. The type strain is W-BA7 T ( = KCTC 42175 T = CECT 8670 T ).